The beaver facilitates species richness and abundance of terrestrial and semi-aquatic mammals - Nummi, Petri; Liao, Wenfei; Huet, Ophélie; Scarpulla, Erminia; Sundell, Janne (Global Ecology and Conservation, 2019)
Beavers are ecosystem engineers which are capable to facilitate many groups of organisms. However, their facilitation of mammals has been little studied. We applied two methods, camera trapping and snow track survey to investigate the facilitation of a mammalian community by the ecosystem engineering of the American beaver (Castor canadensis) in a boreal setting. We found that both mammalian species richness (83% increase) and occurrence (12% increase) were significantly higher in beaver patches than in the controls. Of individual species, the moose (Alces alces) used beaver patches more during both the ice-free season and winter. The Eurasian otter (Lutra lutra), the pine marten (Martes martes) and the least weasel (Mustela nivalis) made more use of beaver sites during the winter. Our study highlights the role of ecosystem engineers in promoting species richness and abundance, especially in areas of relatively low productivity. Wetlands and their species have been in drastic decline during the past century, and promoting facilitative ecosystem engineering by beaver is feasible in habitat conservation or restoration. Beaver engineering may be especially valuable in landscapes artificially deficient in wetlands. (c) 2019 The Authors. Published by Elsevier B.V. This is an open access article under the CC BY-NC-ND license (http://creativecommons.org/licenses/by-nc-nd/4.0/). Peer reviewed